2021
DOI: 10.3389/fcimb.2021.782805
|View full text |Cite
|
Sign up to set email alerts
|

Oral Colonization by Entamoeba gingivalis and Trichomonas tenax: A PCR-Based Study in Health, Gingivitis, and Periodontitis

Abstract: BackgroundThe etiology of periodontitis remains unclear, as is the place of gingivitis in its pathophysiology. A few studies linked the colonization by oral parasites (Entamoeba gingivalis and Trichomonas tenax) to periodontal disease and its severity. The aim of the current study was to estimate the prevalence of these oral parasites among healthy individuals, and in patients with gingivitis and periodontitis in Jordan.MethodsThe study was conducted during July 2019–December 2019. Samples were composed of sal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 62 publications
2
19
1
Order By: Relevance
“…In the periodontitis group, the prevalence of T. tenax among individuals with generalized or localized conditions is 19.6% and 0.0%, respectively ( p = 0.039). Furthermore, the odds ratios with T. tenax infection between periodontitis and healthy groups, and between periodontitis and gingivitis groups are 4.7 (95% CI: 1.0–21.8, p = 0.045) and 7.2 (95% CI: 1.5–33.8, p = 0.013), respectively [ 11 ]. In a study of 92 samples of canine plaque using touchdown PCR and next generation sequencing, the proportion of Trichomonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…In the periodontitis group, the prevalence of T. tenax among individuals with generalized or localized conditions is 19.6% and 0.0%, respectively ( p = 0.039). Furthermore, the odds ratios with T. tenax infection between periodontitis and healthy groups, and between periodontitis and gingivitis groups are 4.7 (95% CI: 1.0–21.8, p = 0.045) and 7.2 (95% CI: 1.5–33.8, p = 0.013), respectively [ 11 ]. In a study of 92 samples of canine plaque using touchdown PCR and next generation sequencing, the proportion of Trichomonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…Electron microscopic studies reveal the presence of Entamoeba gingivalis ( E. gingivalis ) and Trichomonas tenax ( T. tenax ) and free living amoebae in many cases with and without diseases. Its presence is influenced by the host factors showing a mixed composition together with its prominent role along with bacteria and fungi [68] . In patients with genetic diseases, a highest prevalence of E. gingivalis and T. tenax is observed among the age group of 41–50 years portraying its role in the oral microbiome and in inducing diseases upon the alteration of the homeostasis [69] .…”
Section: Oral Parasitesmentioning
confidence: 99%
“…In recent years, several PCR-based studies showed that E. gingivalis was significantly increased in periodontal pockets of periodontitis. The prevalence in patients with periodontitis and in individuals with periodontal health was 74-88.9% (Zaffino et al, 2019;Bao et al, 2020;Dubar et al, 2020;Yaseen et al, 2021) and 3.3-47.9%, respectively (Bao et al, 2020;Dubar et al, 2020;Yaseen et al, 2021). In a study of the transcriptional activity of periodontal pocket microbiota, E. gingivalis had the second highest abundant rRNA found in periodontitis after human rRNA.…”
Section: Introductionmentioning
confidence: 96%